2020
DOI: 10.1016/j.preteyeres.2020.100849
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicle therapy for retinal diseases

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 117 publications
0
88
0
Order By: Relevance
“…In addition to replacement and neurotrophic mechanisms based on stem/progenitor cells, the latest studies have focused on extracellular exosomes secreted by stem cells as a potential therapy for RD. Several studies have identified that some types of MSCs secrete exosomes (MSC-Exo), mainly adipose, bone marrow and umbilical MSCs 45 . Exosomes are cell-derived nanovesicles that have low toxicity, low risk of immunological rejection, exquisite target-homing specificity and potential for drug/gene delivery 115 .…”
Section: Stem Cell-derived Exosomes For Rd Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to replacement and neurotrophic mechanisms based on stem/progenitor cells, the latest studies have focused on extracellular exosomes secreted by stem cells as a potential therapy for RD. Several studies have identified that some types of MSCs secrete exosomes (MSC-Exo), mainly adipose, bone marrow and umbilical MSCs 45 . Exosomes are cell-derived nanovesicles that have low toxicity, low risk of immunological rejection, exquisite target-homing specificity and potential for drug/gene delivery 115 .…”
Section: Stem Cell-derived Exosomes For Rd Treatmentmentioning
confidence: 99%
“…Exosomes are cell-derived nanovesicles that have low toxicity, low risk of immunological rejection, exquisite target-homing specificity and potential for drug/gene delivery 115 . Accordingly, exosome-based therapy is gaining research attention for multiple diseases throughout the body 45 . For instance, scientists have found that MSC-Exo has a prominent therapeutic effect in central nervous system diseases, such as stroke 116,117 , Alzheimer's disease 118 and spinal cord injury 119 .…”
Section: Stem Cell-derived Exosomes For Rd Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…They are considered signaling mediators between cells due to their capability of transporting and delivering proteins, mRNA, miRNA, and lipids. EV are gaining attraction as a candidate treatment for ocular diseases and have already been tested in many retinal damage models, such as glaucoma, retinal ischemia, autoimmune uveitis, and diabetic retinopathy, with promising results (Mead and Tomarev, 2020). Interestingly, it is becoming evident that the miRNA component of EV plays a relevant contribution to the protective action of EV.…”
Section: Microrna-based Approachesmentioning
confidence: 99%
“…including for the treatment of neurodegenerative diseases (Sarko andMcKinney 2017, Mead andTomarev 2020). However, their use for the treatment of retinal degenerations is largely in its infancy (reviewed in (Mead and Tomarev 2020). Hajrasouliha et.…”
Section: Exosomes As Mediators Of Phototransductionmentioning
confidence: 99%